Doing marketing research : alternative methods for market sensing - Lawson, Alison; Hancock, Charles (Writer on marketing) (Routledge, 2025)
"Traditional research methods in marketing can be illuminating when used well, but all too often their results fail to provide the depth of understanding that organisations need to anticipate market needs. Doing Marketing Research enables researchers to get greater depth and meaning from their research and organisations to make smarter strategic decisions. This unique book explains market sensing simply and practically and demonstrates how it can benefit researchers. It teaches non-mainstream and alternative research methods, which facilitate innovative research design and achieve deep insights into the mindsets of consumers. The methods explored in this book include sensory research using ZMET, discourse analysis, consumer ethnography, social media networks, narrative and storytelling and gamification. This 2nd edition has been fully updated to include several new chapters covering newer methods and topics, including the Delphi method, archival research, visual methods and the decolonisation of research. With a wealth of examples, diverse case studies and pedagogy, such as seminar activities to aid student learning, this textbook is recommended and core reading for advanced undergraduate and postgraduate students studying Marketing Research, Business Research Methods more generally, as well as marketing practitioners. Online resources include PowerPoint lecture slides"-- Provided by publisher.
First edition published by Routledge 2016.
Keywords: Marketing research -- Methodology.; Consumers -- Research -- Methodology.; Qualitative research -- Methodology.; elektronické knihy; electronic books